2012
DOI: 10.2106/jbjs.k.00944
|View full text |Cite
|
Sign up to set email alerts
|

Post-Splinting Radiographs of Minimally Displaced Fractures: Good Medicine or Medicolegal Protection?

Abstract: Post-splinting radiographs of non-displaced and minimally displaced fractures that do not undergo manipulation before or during immobilization are associated with longer ER waits, additional radiation exposure, and increased health-care costs without providing helpful information. While certain circumstances call for additional imaging, routine performance of post-splinting radiography of non-displaced or minimally displaced fractures should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…It is questionable whether routine imaging following the initial follow-up (that is, after 2 weeks), after which definitive treatment is established (being surgical or conservative), is justified [8]. Three retrospective studies have suggested that radiographs performed beyond the 2-week follow-up result in longer waiting room visits, unnecessary radiation exposure and increased healthcare costs without providing additional clinical information which impacts clinical decision-making [8-10]. Alongside the clinical question about the justification of the radiographs after the initial follow-up period, a cost-effectiveness analysis is indicated as the current protocols appear not to be cost effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is questionable whether routine imaging following the initial follow-up (that is, after 2 weeks), after which definitive treatment is established (being surgical or conservative), is justified [8]. Three retrospective studies have suggested that radiographs performed beyond the 2-week follow-up result in longer waiting room visits, unnecessary radiation exposure and increased healthcare costs without providing additional clinical information which impacts clinical decision-making [8-10]. Alongside the clinical question about the justification of the radiographs after the initial follow-up period, a cost-effectiveness analysis is indicated as the current protocols appear not to be cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is questionable whether routine imaging following the initial follow-up (that is, post 2-weeks) is justified [8]. Justification for obtaining radiographs beyond the initial follow-up includes documentation of splint application, resident education, assurance that the fracture has not displaced, and medico-legal protection against claims of unintended harm [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Although our study did not ask respondents about their practices regarding postsplinting radiographs of minimally displaced fractures, it is worthwhile to note that there has been some recent investigation into this topic. Chaudhry et al 7 found that post-splinting radiographs of nondisplaced/minimally displaced fractures that do not undergo manipulation during or before immobilization do not have clinical utility but do increase costs, wait times, and radiation exposure. They concluded that post-splinting radiographs in these cases could be for-gone.…”
Section: Percent Of Postoperative Visits For Asymptomatic Patients Wimentioning
confidence: 99%
“…Similarly, Chaudhry et al studied post-splinting radiographs in minimally displaced fractures and found that post-splinting radiographs of minimally displaced or nondisplaced fractures that do not undergo manipulation before/during immobilization do not provide helpful information but do lead to increased health care costs, radiation exposure, and emergency room waits. 7 They concluded that routine performance of post-splinting radiography in these cases should be discouraged.…”
mentioning
confidence: 99%